Arteterapia no Centro de Atenção Psicossocial III: uma estratégia para a Promoção da Saúde - Bolzani, Berliete (2022)
This thesis approaches art therapy in therapeutic contexts, as the expression of patients who have some kind of mental disorder. The Psychiatric Reform is a milestone in the organization of mental health policy in Brazil. It is characterized by the transformation of the care model towards new therapeutic proposals in mental health and the Psychosocial Care Centers (CAPS) are the reference and treatment services, with therapeutic workshops that promote expressiveness and greater social and family integration. Art therapy can be used as an instrument to enhance this process, expanding perception, restoring self-esteem and awakening users' creativity. In this perspective, the aim of this study was to develop Art Therapy workshops in the CAPS III care, aiming to identify possibilities of its use as a therapeutic resource in mental health treatment. The workshops took place weekly and the activities were transcribed and recorded in a field diary. This is research with a qualitative approach, characterized as participant observation research, which adopted the theoretical frameworkphenomenological method of Carl Gustav Jung, for data analysis. Four art therapy workshops were held (drawing, painting, fairy tales and tarot), with 11 CAPS user participants. There were 38 meetings with the group, providing the perception and selfexpression of emotions, expanding the perception of problems to identify solutions, facilitating the self-organization of possibilities to overcome everyday pain. The intervention, through art therapy and creativity, strengthened feelings of selfconfidence and autonomy, enhancing and valuing the improvement in emotional balance and minimizing the negative effects resulting from psychopathology. Through artistic expressions, some questions can be given voice, rescuing identity and vitality, pleasure and well-being, which often seem lost in painful situations. From this experience, it can be considered that art therapy, inserted in the Integrative and Complementary Practices (PICs) of the Unified Health System, is still a field of work to be explored, as a strategy for welcoming individuals in mental suffering and social fragility, in the proposals of deinstitutionalization and psychosocial rehabilitation strategies, with the objective of stimulating the protagonism of these users, also favoring new ways of being, feeling and acting for groups. Keywords: Art therapy. Mental Health. Integrative and Complementary Practices